FROM STEAM TECHNOLOGY IN PRESCHOOL ORGANIZATIONS EFFECTIVE METHODS OF USE - Sotimboyeva Yulduzoy Salohiddinovna (Web of Journals Publishing, 2024)
This article explores effective ways to incorporate STEAM (science, technology, engineering, arts, and mathematics) technology into preschool organizations. It discusses the benefits of integration with STEAMerta in childhood education, provides practical implementation strategies, presents successful implementation outcomes, and provides insights into the future of steam preschool education.
Keywords: STEAM technology, preschool education, early childhood learning, applied education, interactive education, STEM education, game-based learning, creativity, problem solving, critical thinking.